A method for calculation of lateral displacements of buildings under distributed loads - Süleyman Aydın; Kanat Burak Bozdoğan; Duygu Öztürk (MANAS: Journal of Engineering)
Lateral displacement is a vary important parameter that we need to calculate when structures are subjected to lateral loads like earthquake and wind loads. In this study, a method is proposed for lateral displacement calculation of structures with different structural systems in different planes. This method is based on the continuum system calculation model. The method suggested in the literature for only top displacement in the case of uniform loading, is developed in this study for the calculation of displacements at each storey level and also in both uniform and triangular loading conditions. At the end of the study, twenty-eight storey building with shear wall-frame bearing system, which was taken from the literature, was solved with the presented method and Finite Element Method. The shear walls were modelled with three different element types for the analysis with the Finite Element Method with structural engineering program used. The results, obtained from the Continuum Method and Finite Element Method were presented in tables and by figures. Thus, the compatibility of the proposed method with the classical Finite Element Method was investigated. From the compared results of the method and the literature or finite element models it was seen that the method used for the case of uniform or triangular distributed loading gives very close results.